Ziarah Perspektif Kajian Budaya (Studi Pada Situs Makam Mbah Priuk Jakarta Utara ) - Syahdan Syahdan (Jurnal Studi Agama dan Masyarakat, 2017)
Pilgrimage in this study tries to investigate from the perspective of cultural study, they are form (significant), function (application, interaction) and meaning (signifie). This study aimed to obtain information about the process of pilgrimage ritual at the tomb of Mbah Priuk, also trying to comprehend the function and meaning contained in the pilgrimage ritual activities conducted at the tomb of Mbah Priuk. The results obtained in this study show that all the informants who researcher encountered have similar view about Mbah Priuk. The people’s motive who do pilgrimage, in general, is to pray and make Mbah Priuk as a mediator. The unique ritual done by pilgrims is throwing banknotes or coins into a small pond. In this ritual many pilgrims choose the pool eventhough there is already a place to put the money provided by the cemetary organizer.